Going public with pedagogical inquiries: SoTL as a methodology for faculty professional development - Fanghanel, Joëlle (Teaching and Learning Inquiry, 2013)
In this paper, I discuss SoTL as a methodology for the professional development of academics. I propose that as an agentic form of inquiry that focuses on processes, boundary-crossing, and making public its findings, SoTL is a sophisticated methodology that brings the activities of teaching and research in close alignment, and contributes to developing an approach to inquiry that differs from what I have called “managed” research. I propose that, as a methodology for professional development, SoTL provides a space for dialogic critique of singular investigations into practice that contribute to advancing individual and collective knowledge of the field of higher education. I argue that in a context where approaches to practice have become driven by competitivity and international rankings that rely on objectivist understandings of practice for their judgments, SoTL presents an alternative, rich model of practice.